Helicobacter pylori Infection Associated with Type 2 Diabetes: A Case–Control Study - Taha, Aza B. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2024)
Helicobacter pylori (Hp) is a spiral Gram-negative bacterium that causes gastritis and peptic ulcers. It has been identified as a risk factor for gastric cancer and has become a significant global health burden. This is further complicated by being associated with increasing the prevalence of Type 2 diabetes (T2D). The study aimed to evaluate the possible associations between Hp infection and T2D, as well as its impact on glycated hemoglobin. A 1:1 matching case–control study is conducted on 548 individuals with T2D as cases and 548 controls, and a 14C-urea breath test is used to determine the presence of Hp infection. All diabetic subjects are tested for glycated hemoglobin, and binary logistic regression analysis is used to evaluate the associations between Hp infection and T2D. The prevalence of Hp infection is higher among cases (58.94%) than control subjects (38.69%) (p < 0.001). A significant association is observed between Hp infection and T2D according to logistic regression analysis (OR = 2.275; 95% CI: 1.786-2.898; p < 0.001), and there is a significant association (p = 0.022) between glycated hemoglobin levels and Hp infection. Individuals infected with Hp had a higher-level glycated hemoglobin (7.84 ± 1.797) than Hp-negative individuals (p < 0.001). Hp infection is associated with elevated glycated hemoglobin levels. Type 2 diabetes is considered a risk factor for developing Hp infection.